The promise and reality of social and cultural metrics - Douglas L. Bessette (Resilience Alliance, 2020)
In addition to evaluating the economic, ecological, and health impacts of major public policy initiatives, impact assessments typically also need to identify and evaluate an action's social and cultural (S/C) impacts. A wide range of S/C metrics have been suggested, and guidelines exist to help ensure their thoughtful and comprehensive development. Nevertheless, many of the S/C concerns identified as part of impact assessments remain vague, are difficult to measure or understand, and are more closely attuned to existing data than to concerns expressed by stakeholders or residents of Indigenous communities. Furthermore, S/C impacts are often deemphasized or, in some cases, outright ignored during project generation and as part of final decisions made by elected officials. Here, we examine the promise of well-designed S/C metrics and contrast it with the reality of how they are commonly deployed, with specific reference to four case studies in North America: municipal planning decisions in Oregon, wildlife decisions in Ohio, renewable energy decisions in Michigan, and pipeline decisions in the western United States and Canada. We argue the importance of moving beyond assessment to decision making, pointing out five reasons why critical S/C impacts are often neglected, and presenting recommendations for the design of clearer, more comprehensive metrics that will contribute to more socially responsive policy choices.